Enhancement of photoconversion efficiency and light harvesting ability of TiO2 nanotube-arrays with Cu2ZnSnS4. (22nd August 2022) - Al-Shihabi Al-Ani, Athil; Tokay, Begum; Zhu, Wen; Chen, George Z.
Abstract: We report an underpotential deposition (UPD) route of Cu2 ZnSnS4 /TiO2 nanotube arrays (TiO2 -NTAs) in which the Kesterite (Cu2 ZnSnS4 ) was employed as a sensitizer to enhance the photoconversion efficiency of the TiO2 -NTAs. Cu2 ZnSnS4 was simultaneously coated on TiO2 -NTAs by depositing its constituent metals from the precursor ions via electrochemical atomic layer deposition (EC-ALD) and subsequent annealing. The detailed synthesis process, the surface morphology, crystalline structure, photoelectrochemical properties and hydrogen production rate of the as-prepared Cu2 ZnSnS4 /TiO2 -NTAs were discussed. Thickened TiO2 nanotubes were observed, suggesting that the Cu2 ZnSnS4 coating was about 5 ± 0.5 nm. The results showed that the light harvesting of TiO2 -NTAs has an obvious improvement after sensitizing them with Cu2 ZnSnS4 . In comparison with pure TiO2 -NTAs, a two-fold increment in photoconversion efficiency was achieved using the composite of Cu2 ZnSnS4 /TiO2 -NTAs. The novel photoanode of CZTS/TiO2 NTAs achieved a maximum hydrogen generation rate of 49 ml h −1  cm −2 . Graphical abstract: Image 1 Highlights: Cu, Zn, Sn and S were simultaneously deposited onto TiO2 nanotube arrays. The bandgap was narrowed from 3.1 eV of pure TiO2 NTAs to 2.43 eV of CZTS/TiO2 NTAs. The CZTS/TiO2 NTA photoanode demonstrated a max H2 generation rate of 49 ml h −1  cm −2 . The Cu2 ZnSnS4 coating was about 5 ± 0.5 nm.